2018
DOI: 10.20302/nc.2018.27.16
|View full text |Cite
|
Sign up to set email alerts
|

New data on Turkish hypogeous fungi

Abstract: In this study, three species of hypogeous fungi are reported in different regions of Anatolian peninsula. Of these, Hydnocystis piligera is presented as the first record of this genus for Turkish mycobiota, while Melanogaster variegatus and Octaviania asterosperma are given as new locality records for Turkey. Macroscopic and microscopic photographs along with description of the newly recorded taxa are presented.Provedenim istraživanjem zabilježene su tri vrste podzemnih gljiva u različitim regijama poluotoka A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Both taxa have previously been presented from Turkey only once. Alpova diplophloeus is a member of the order Boletales and sixteen hypogeous members of this order belonging to four families and five genera (Octaviania Vittad., Alpova C.W.Dodge, Melanogaster Corda, Rhizopogon Fr., Sclerogaster R.Hesse) have so far been reported from Turkey (Demirel, 1996;Kaşık et al, 2002;Sesli and Castellano, 2009;Uzun et al, 2014;Sesli and Moreau, 2015;Türkoğlu et al, 2015;Elliot et al, 2016;Allı et al, 2017;Öztürk et al, 2017;Türkekul, 2017;Kaygusuz et al, 2018;Uzun et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…Both taxa have previously been presented from Turkey only once. Alpova diplophloeus is a member of the order Boletales and sixteen hypogeous members of this order belonging to four families and five genera (Octaviania Vittad., Alpova C.W.Dodge, Melanogaster Corda, Rhizopogon Fr., Sclerogaster R.Hesse) have so far been reported from Turkey (Demirel, 1996;Kaşık et al, 2002;Sesli and Castellano, 2009;Uzun et al, 2014;Sesli and Moreau, 2015;Türkoğlu et al, 2015;Elliot et al, 2016;Allı et al, 2017;Öztürk et al, 2017;Türkekul, 2017;Kaygusuz et al, 2018;Uzun et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…Only one hypogeous member of Boletaceae within the genus Octaviania Vittad. has been reported from Turkey (Türkoğlu et al, 2015;Kaygusuz et al, 2018). Current checklists on Turkish macromycota (Solak et al 2015;Sesli and Denchev 2014) and the contributions published after the checklists (Sadullahoğlu and Demirel, 2018;Uzun et al, 2018;Acar et al, 2019;Keleş, 2019;Uzun and Kaya, 2019a,b;Yakar et al, 2019) indicate that Wakefieldia macrospora (Hawker) Hawker hasn't so far been reported from Turkey.…”
Section: Introduction Wakefieldiamentioning
confidence: 99%
“…The members of the genus are characterized by a globose to rounded and usually stalked fruiting bodies, warty or smooth and brownish to lighter membranous peridium, globular 8-spored asci, more or less broadly ellipsoidal spores, and substrates of animal residues such as hairs, plumes, bones, hooves and horns (Ward, 1899;Medardi, 2006). Though 5 species of the genus were described (Kirk et al, 2008), none of them were reported from Turkey according to the current literature (Sesli and Denchev 2014;Solak et al 2015) and the latest contributions (Kaşık et al, 2017;Akçay et al, 2018;Işık and Türkekul, 2018a,b;Kaya, 2015;Kaya et al, 2016;Kaya and Uzun, 2018;Kaygusuz et al, 2018;Sadullahoğlu and Demirel, 2018;Sesli, 2018;Uzun et al, 2018;Keleş, 2019;Şelem et al, 2019;Türkekul and Işık, 2019) presented after the checklists.…”
Section: Introductionmentioning
confidence: 99%